2005
DOI: 10.1142/s0192415x0500276x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Vagal Modulation by Acupuncture at Neiguan Point in the Healthy Subjects

Abstract: Acupuncture at the Neiguan (P6) point has been shown to lessen nausea and vomiting which are related to vagal modulation. This study investigated whether acupuncture at the P6 point could improve vagal modulation by using heart rate variability analysis. We compared the heart rate variability measures of 39 subjects receiving acupuncture at the P6 point, 38 subjects receiving sham acupuncture, and 34 subjects receiving no treatment at all. The normalized high-frequency power was used as the index of vagal modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 9 publications
3
66
0
5
Order By: Relevance
“…There are many studies showing that acupuncture regulates the autonomic nervous system. 28,[30][31][32][33][34] In particular, ST 36 and PC 6, the acupoints used in this study, have been shown to balance the autonomic nervous system, 30 suppress heart rate and low-frequency/high-frequency ratio, 33 and normalize highfrequency power. 34 Hence, one can speculate that the effect of acupuncture on nocturnal BP dipping might result, in part, from suppression of the sympathetic tones and increased parasympathetic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies showing that acupuncture regulates the autonomic nervous system. 28,[30][31][32][33][34] In particular, ST 36 and PC 6, the acupoints used in this study, have been shown to balance the autonomic nervous system, 30 suppress heart rate and low-frequency/high-frequency ratio, 33 and normalize highfrequency power. 34 Hence, one can speculate that the effect of acupuncture on nocturnal BP dipping might result, in part, from suppression of the sympathetic tones and increased parasympathetic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been reported to normalize decreased parasympathetic nerve activity, 18 which is thought to be the cause of the absence of nocturnal BP dipping. 19 It was therefore hypothesized that acupuncture would regulate the circadian rhythm of BP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, electroacupuncture at Neiguan (Pc-6; located in the groove caudal to the flexor carpi radialis and cranial to the superficial digital flexor muscles) significantly increases vagal activity, as measured by spectral analysis of heart rate variability. 8,9 In contrast, electroacupuncture at Hegu (Li-4; located at the junction of the first and second metacarpal bones) increases sympathetic tone, as evidenced by elevation of blood pressure and increased renal and adrenal nerve activities. 10,11 Based on these data, we tested the hypothesis that electroacupuncture at specific acupoints could inhibit systemic inflammatory responses and improve survival via its impact on the ANS in a rat model of sepsis (systemic administration of endotoxin).…”
mentioning
confidence: 99%
“…At enrolment, patients were given a chart to annotate the occurrence and duration of paroxysmal symptomatic episodes. All patients of this latter group as well as patients with persistent AF randomized to acupuncture underwent 10 acupuncture sessions of 15-20 min duration on a once a week basis in the following spots ( Figure 2): PC-6 (Neiguan in modern Chinese language), which is reported to have a modulating effect on the autonomic nervous system, with a mainly vagomimetic and sympathicolytic action [16][17][18] ; HT-7 (Shenmen in modern Chinese language), which is reported to have a calming and sedative effect on cardiac excitability [19] ; BL-15 (Xinshu in modern Chinese language), which is reported to have a modulating effect on the autonomic nervous system [20] . The effects of acupuncture were evaluated in a 12 mo follow-up period in both sets of patients.…”
Section: Patient Populationsmentioning
confidence: 99%